2013
DOI: 10.1016/j.jalz.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Florbetapir (F18‐AV‐45) PET to assess amyloid burden in Alzheimer's disease dementia, mild cognitive impairment, and normal aging

Abstract: Objective To evaluate the performance characteristics of florbetapir F 18 PET in patients with Alzheimer’s disease dementia (AD), mild cognitive impairment (MCI) and healthy control subjects (HC). Methods Florbetapir PET was acquired in 184 subjects (45 AD, 60 MCI, and 79 HC) within a multi-center phase 2 study. Amyloid burden was assessed visually and quantitatively and classified as positive or negative. Results Florbetapir PET was visually rated amyloid positive in 76% of AD, 38% of MCI and 14% of HC. 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
148
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 209 publications
(179 citation statements)
references
References 55 publications
27
148
0
Order By: Relevance
“…Consistent with previous studies, neocortical and subcortical gray matter 18 Fflorbetapir retention was increased in patients with AD, compared with healthy controls (21,22). In line with the primary study hypothesis, 18 Fflorbetapir binding was significantly increased in the cortical and subcortical gray matter of patients with AD relative to those with FTD.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous studies, neocortical and subcortical gray matter 18 Fflorbetapir retention was increased in patients with AD, compared with healthy controls (21,22). In line with the primary study hypothesis, 18 Fflorbetapir binding was significantly increased in the cortical and subcortical gray matter of patients with AD relative to those with FTD.…”
Section: Discussionsupporting
confidence: 89%
“…Fourteen percent of cognitively normal cases were interpreted with complete interreader agreement as ␤-amyloid-positive, both with only qualitative assessment and with the aid of SUVr (On-line Table). These findings are congru- ent with prior imaging studies 13 and are within range of cortical ␤-amyloid deposition seen in postmortem case studies in cognitively normal, mildly cognitively impaired, and patients with Alzheimer disease. [33][34][35] Our findings also demonstrate that the relationship between cognitive decline and the amount of cortical ␤-amyloid deposition is variable because we see studies with positive findings in all of our experimental groups (normal, EMCI, LMCI, and AD) and they are compatible with prior pathologic studies.…”
Section: 712supporting
confidence: 82%
“…5,12 However, SUVr are onerous to calculate manually, and manual placement of ROIs is prone to variability. Computer assistance could provide an easier method to incorporate SUVr into the interpretation process, 13,14 and semiautomated software has been developed to facilitate SUVr calculations. The current standardized methodology for amyloid PET brain interpretation does not use SUVr, 14 which might be useful to improve reader agreement.…”
mentioning
confidence: 99%
“…15,16 Our finding of a false-positive (1 HTN-ICH patient who was florbetapir-positive) likely reflects the background rate of approximately 14% of otherwise healthy older adults who have an amyloid-positive scan. 21 One previous study found that 4 out of 9 cognitively healthy older controls had high PiB retention, the highest reported rate of false positivity in amyloid imaging field but the sensitivity to detect CAA was still excellent (91%) in this particular study. 38 It is plausible that the high specificity that we found might suffer in patients 80 and older due to increased incidence of asymptomatic amyloid positivity.…”
Section: Resultssupporting
confidence: 42%
“…All 19 participants underwent a florbetapir-PET scan using procedures described previously. 21 All participants received a single IV bolus of 370 MBq (10 mCi) of florbetapir F18. After transmission data were acquired, a 20-minute PET acquisition for florbetapir was acquired in 4 3 5-minute frames beginning 50 minutes postinjection.…”
Section: Classification Of Evidencementioning
confidence: 99%